Moringa oleifera Lam. leaf supplementation enhances egg quality parameters and commercial value in laying hens - Martínez, Alejandro; Vayas, Tamara; Landázuri, Andrea C.; Yánez-Ortiz, Iván; Ortiz-Manzano, Mario; Mejía, Jaime; Ramírez-Cárdenas, Lucía; Alvarez-Suárez, José M.; Lagos, Andrés S.; Díaz, Ramiro F. (Frontiers in Nutrition, 2025)
BackgroundMoringa oleifera Lam. leaf supplementation shows promise for enhancing egg quality in commercial poultry production where feed costs comprise 60%–70% of total expenses. However, systematic dose–response studies evaluating optimal supplementation levels remain limited. This study evaluates graduated Moringa supplementation effects (1, 1.5, 2, and 2.5%) on egg quality parameters and production performance in commercial laying hens.MethodsOne hundred twenty-five Lohmann Brown hens (33-week-old) were randomly allocated into five groups (n = 25) over 10 weeks. Four groups received Moringa supplementation at 1, 1.5, 2, and 2.5% inclusion rates; controls received standard feed. Environmental conditions maintained 12.5 ± 1 °C with commercial feed provided at 114.8 g per hen per day between 7:30–9:30 a.m. Moringa nutritional analysis used standardized methods (Kjeldahl, Soxhlet, atomic absorption spectrophotometry). Weekly egg quality assessment employed DET6500® Digital Egg Tester evaluating weight, eggshell hardness, thickness, albumin height, Haugh unit, and yolk coloration. Statistical analysis used GLMM with Bonferroni post-hoc testing (p < 0.05).ResultsEcuadorian Moringa leaves demonstrated exceptional nutritional composition: 36.08% protein, superior antioxidant capacity (DPPH: 326.5 μmol TE/g, ABTS: 823 μmol TE/g), and high mineral density (1,408 mg calcium/100 g, 9.1 g iron/100 g). The 2.5% supplementation significantly improved egg weight (4.2% increase, p < 0.05), albumin height (7.3% vs. 2% group, p < 0.05), and Haugh units (p < 0.05). All Moringa groups showed enhanced yolk coloration versus controls (12.78–12.96 vs. 12.40, p < 0.05). While 1% supplementation produced maximum eggshell hardness (5.01 Kgf), 2.5% provided optimal overall quality enhancement. Production performance remained stable across groups. Quality improvements stabilized by weeks 6–8.ConclusionMoringa supplementation at 2.5% inclusion rate effectively enhances multiple egg quality parameters without compromising production efficiency. Comprehensive improvements enable potential Grade A to AA classification upgrade, representing 12%–15% market value increase versus 3%–4% feed cost increase. Ecuadorian Moringa’s superior nutritional profile (complete amino acid composition, exceptional antioxidant capacity, high mineral density) provides the mechanistic foundation for observed improvements. These findings establish evidence-based Moringa supplementation protocols for sustainable premium egg production in commercial operations.